2016
DOI: 10.1016/j.puhe.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards community pharmacy attributes and preferences for methods for promotion of public health services

Abstract: Objective: To identify attitudes towards pharmacy characteristics and promotional methods for selected pharmacy public health services (lifestyle advice and screening for cardiovascular risk factors) among different sectors of the general public. Study design:Cross-sectional survey, using a previously validated questionnaire.Methods: Three survey methods were used, across 15 areas of England, to maximise diversity: face-to-face, telephone and self-completion of paper questionnaires. Responses to closed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…While few had used any pharmacy PH services, many were willing to use them once they became aware of what was offered. This echoes other studies that have shown that pharmacy services are not fully utilised and are not well advertised …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While few had used any pharmacy PH services, many were willing to use them once they became aware of what was offered. This echoes other studies that have shown that pharmacy services are not fully utilised and are not well advertised …”
Section: Discussionsupporting
confidence: 79%
“…This echoes other studies that have shown that pharmacy services are not fully utilised and are not well advertised. [25][26][27] This study has identified that the public are open to the incorporation of digital health tools into pharmacy services, with younger demographics being most keen. They indicated that they found SM health pages and MH apps to be reliable, useful and convenient, a finding noted previously by Cain et al [28] in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Study designs using questionnaires (n = 14, 41%), semi‐structured interviews (n = 8, 24%) and focus groups (n = 6, 18%) made up the vast proportion of studies. Three mixed‐methods studies involved the use of questionnaires and semi‐structured interviews, one combined observations and semi‐structured interviews .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 2 studies were discrete choice experiments . Most of the studies (n = 28, 82%) were published from 2010 onwards . Seven studies related to pharmacist prescribing which, although not exclusive to community pharmacy, provides valuable insights into opinions of pharmacists’ extended roles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation